Retrospective study of immunization errors reported in an online Information System - Tânia Cristina Barboza; Rafael Alves Guimarães; Fernanda Raphael Escobar Gimenes; Ana Elisa Bauer de Camargo Silva
Objective: to analyze the immunization errors reported in an online Information System. Method: retrospective study conducted with data from the Adverse Event Following Immunization Surveillance Information System. Immunization errors were analyzed with respect to demographic characteristics and the vaccination process. Frequencies and error incidence rates have been calculated. Binomial and chi-square tests were used to verify differences in the proportions of the variables. Results: 501 errors were analyzed, the majority involving routine doses (92.6%), without Adverse Event Following Immunization (90.6%) and in children under five years old (55.7%). The most frequent types of errors were inadequacy in the indication of the immunobiological (26.9%), inadequate interval between doses (18.2%) and error in the administration technique (14.2%). The overall error incidence rate was 4.05/100,000 doses applied; the highest incidences of routine vaccines were for human rabies vaccine, human papillomavirus and triple viral; the incidence rate of errors with Adverse Events Following Immunization was 0.45/100,000 doses applied. Conclusion: it was found that immunization errors are a reality to be faced by the health systems, but they are amenable to prevention through interventions such as the adoption of protocols, checklists and permanent education in health.